Diet Quality Differs by Race/Ethnicity Among Mothers and Their Children from Supplemental Nutrition Assistance Program?Education Households (Mary Ann Liebert, 2021)
Purpose: To investigate diet quality by race/ethnicity among mothers and their children from low-income households throughout California. Methods: Cross-sectional telephone surveys of mothers and their children from randomly sampled households using a validated 24-h dietary assessment. Healthy Eating Index-2015 (HEI-2015) scores were calculated. Results: The mean HEI-2015 scores were lower for African American and white mothers and children compared with Latinx mothers and children. Conclusion: Addressing poor levels of overall diet quality among African American and white mothers and children from low-income households is of public health importance. Reasons for Latinxs' superior diet quality may include limited acculturation to U.S. culture.